How does FDAC Succeed with Parents with Substance Misuse Problems? Exploring Relational Practices within the English Family Drug and Alcohol Court. (9th October 2018) - Harwin, Judith; Ryan, Mary; Broadhurst, Karen
Abstract : Parental substance misuse is a significant risk factor for child maltreatment and is frequently involved in care proceedings. Outcomes are often poor and family reunification is prone to breakdown. In this article, the contribution of the English Family Drug and Alcohol Court (FDAC) is examined. Adapted from the US family drug treatment court model, FDAC offers a radically different approach to ordinary care proceedings by treating parents as well as adjudicating. The article draws on a mixed‐methods evaluation of FDAC which reports better recovery and reunification rates than ordinary court. It presents findings from interviews with 42 parents and 154 court observations of 89 cases, focusing on FDAC's relational practices. The article concludes that these relational practices offer hope to substance‐misusing parents and that the approach merits wider attention because of its therapeutic potential and distinctive approach to justice. 'The contribution of the English Family Drug and Alcohol Court (FDAC) is examined' Key Practitioner Messages: FDAC is a helpful approach to care proceedings for substance‐misusing parents. Parents value clear, consistent and honest messages about their progress when delivered in the context of trusted relationships and intensive support. Parents need holistic help that takes into account damaging early‐life experiences. 'Parents need holistic help that takes into account damaging early‐life experiences'